2020
DOI: 10.1161/hypertensionaha.119.13720
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Slow Wave Sleep and Obstructive Sleep Apnea in Prevalent Hypertension

Abstract: Due to frequent abnormal breathing events and their effects on sleep architecture, patients with obstructive sleep apnea (OSA) exhibit decreased amounts of slow wave sleep (SWS). Reduced SWS has been linked to hypertension in community-based studies. We sought to investigate whether SWS percentage modifies the association between OSA and prevalent hypertension. We studied 7107 patients with OSA and 1118 primary snorers who underwent in-laboratory polysomnography. Patients were classified into quartiles of perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 50 publications
2
16
1
Order By: Relevance
“…Furthermore, we found an association between combined OSA and SWS and prevalent hypertension. The higher mean incidence of hypertension (50.2%, 575/1145) observed in our study compared with the three studies mentioned above 17 19 could be explained by the patients with primary snoring and OSA in our cohort. Another study showed that the incidence of hypertension in patients with suspected OSA was 50.8% in 2018, 27 which is in accordance with our study.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Furthermore, we found an association between combined OSA and SWS and prevalent hypertension. The higher mean incidence of hypertension (50.2%, 575/1145) observed in our study compared with the three studies mentioned above 17 19 could be explained by the patients with primary snoring and OSA in our cohort. Another study showed that the incidence of hypertension in patients with suspected OSA was 50.8% in 2018, 27 which is in accordance with our study.…”
Section: Discussioncontrasting
confidence: 61%
“…The authors in this previous study found that the protective effect of SWS on hypertension was highest in quartile 3, not in quartile 4. A recent study 19 showed a significant relationship between SWS and OSA in prevalent hypertension for the first time, and SWS was associated with elevated BP in a dose-dependent manner in OSA. Our findings are consistent with these previous findings.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…22 The "sleep architecture" characterizes the distribution of different stages of sleep and is reportedly related to the risk of cardiovascular diseases. 23 In the present study, the authors showed that higher visit-to-visit BP variability was associated with sleep architecture as reflected by reduced REM sleep duration, thereby suggesting a possible interesting link between quality of sleep and a parameter of long-term BP variability. 22 Concerning the relevant mechanisms of the BP variability in healthy subjects, inflammation induced by sleep disturbances might be another potential pathogenic mechanism.…”
supporting
confidence: 50%
“…1 SAHS is one form of sleep-related breathing disorder, which encompasses obstructive sleep apnoea (OSA), 2 3 mixed sleep apnoea, 4 central sleep apnoea (CSA) 5 and sleep-related hypoventilation. 1 SAHS is a common comorbidity in patients with various diseases and is a risk factor for congestive heart failure, 6 7 myocardial infarction, 8 9 hypertension, [10][11][12] diabetes mellitus, [13][14][15] chronic obstructive pulmonary disease (COPD) [16][17][18][19] and cerebral disease, 20 which are also reasons for intensive care unit (ICU) admission.…”
Section: Introductionmentioning
confidence: 99%